SISTEM PAKAR DIAGNOSA PENYAKIT PADA GANGGUAN PENCERNAAN ORANG DEWASA: Expert System, Forward Chaining, Digestive Disorders, Visual Basic 6.0, Database, SQLyog - Louis, Ahmad; -, Samsidar (LP2M Universitas Nurdin Hamzah, 2018)
Digestion is one of the most important parts of the human body because of digestion in charge of receiving the food to be distributed throughout the body. If digestion is not going well there are times when it will cause indigestion which occurred ketidakyamanan in the abdomen that can bring a variety of symptoms that can be associated with a number of illnesses. Generally indigestion resemblance between the symptoms that sometimes make people diagnose disease commonly occurs without a clear idea of ​​the difference between the disease to each other because of digestive disorders commonly associated with a diet that is not good. Though serious diseases can also occur due to digestive problems. Therefore constructed disease diagnosis expert system for digestive disorders in order to diagnose the early symptoms with the inference method used is a forward chaining which will be read first common symptoms that will point to the specific issues of interest to find a solution. This expert system developed by using VB 6.0 programming language and database SQLyog.